Reduction of serum IGF-I levels in patients affected with Monoclonal Gammopathies of undetermined significance or Multiple Myeloma. Comparison with bFGF, VEGF and K-ras gene mutation - Greco, Claudia; Vitelli, Gaetano; Vercillo, Giuseppe; Vona, Rosa; Giannarelli, Diana; Sperduti, Isabella; Pisani, Francesco; Capoluongo, Ettore; Petti, Maria Concetta; Ameglio, Franco (Journal of experimental & clinical cancer research, 2009)
Background Serum levels of IGF-I in patients affected with multiple myeloma (MM) have been scarcely studied. The present study is aimed to explore this point comparing 55 healthy subjects, 71 monoclonal gammopaties of uncertain significance (MGUS) and 77 overt MM patients. In the same subjects, basic FGF and VEGF, have been detected. All three mediators were analyzed in function of K- ras mutation and melphalan response. Concerning IGF-I, two representative monitoring examples have also been added. Methods Cytokine determinations were performed by commercially available ELISA kits, while K12- ras mutation was investigated on genomic DNA isolated from bone marrow cell specimens by RFLP-PCR assay. Results Significant reductions of IGF-I levels were observed in MGUS and MM as compared with healthy controls. In addition, MM subjects showed significantly decreased serum IGF-I levels than MGUS. Conversely, increasing levels were observed for bFGF and VEGF, molecules significantly correlated. A multivariate analysis corrected for age and gender confirmed the significant difference only for IGF-I values (P = 0.01). K12- ras mutation was significantly associated with malignancy, response to therapy and with significantly increased serum bFGF levels. Conclusion IGF-I reduction in the transition: Controls→MGUS→MM and changes observed over time suggest that IGF-I should be furtherly studied in future clinical trials as a possible monitoring marker for MM.